1998
DOI: 10.1159/000025842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diadenosine Polyphosphates on Systemic and Regional Hemodynamics in Anesthetized Rats

Abstract: Diadenosine polyphoshates (Ap4A, Ap5A, Ap6A) induce vasodilatation or vasoconstriction in various isolated vessels and influence central and peripheral hemodynamics. The influence of diadenosine polyphoshates on hemodynamics was studied in anesthetized rats in vivo. Mean arterial blood pressure (MABP) and heart rate (HR) measured in the carotid artery decreased with Ap4A, Ap5A and Ap6A. Renal blood flow (RBF), femoral blood flow (FBF) and cardiac output (CO) were evaluated by an ultrasonic transit-time method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In anesthetized dogs and pigs, Ap4A caused a decrease in mean arterial pressure [12,13] which we demonstrated recently also for Ap4A, Ap5A and Ap6A [14]. Diadenosine polyphosphates induce negative chronotropic and inotropic responses in guineapig, canine, and human cardiac preparations [1,6,12].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In anesthetized dogs and pigs, Ap4A caused a decrease in mean arterial pressure [12,13] which we demonstrated recently also for Ap4A, Ap5A and Ap6A [14]. Diadenosine polyphosphates induce negative chronotropic and inotropic responses in guineapig, canine, and human cardiac preparations [1,6,12].…”
Section: Introductionmentioning
confidence: 75%
“…The vascular tone in several organs is influenced by diadenosine polyphosphates. In vitro, Ap5A and Ap6A produced transient concentration-dependent contractions of the human umbilical artery [3]; all naturally occurring diadenosine polyphosphates increased the renal vascular tone in anesthetized rats [2,5,14]. Ap3A mediated endothelium-dependent vasodilation in the rat mesenteric artery [15] and endotheliumindependent vasodilation in the rabbit mesenteric artery [16].…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, previous studies have indicated that Ap 4 A reduces ischemic injury in the CNS and heart (Khattab et al, 1998;Ahmet et al, 2000a,b;Wang et al, 2003). Recently, Ap 4 A has been shown to have strong neuroprotective properties mediated by P1 and P4 receptors in primary neuronal culture used as models for stroke and Parkinson's disease (Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The higher contractile potency of ApnA than their degradation products may be reflected by their considerably higher stability in the blood than, for instance, ATP, which is cleaved into adenosine and phosphate within seconds (Lü thje and Ogilvie, 1988;Lü thje, 1989). Although vasocontractile effects of ApnA on the local vascular level are well established, it was repeatedly confirmed that systemically applied ApnA only induce hypotensive effects (Kikuta et al, 1994;Khattab et al, 1998;Steinmetz et al, 2000c). Various studies with animal vascular preparations showed that the purinergically mediated vasoconstrictions are P2X purinoceptor-dependent (Bo and Burnstock, 1993;van der Giet et al, 1998;Steinmetz et al, 2000a,c).…”
Section: Discussionmentioning
confidence: 99%